2011
DOI: 10.1007/s13105-011-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

Leptin increases prostate cancer aggressiveness

Abstract: Recent studies indicate that adipose tissue and adipocytokines might affect the development of prostate cancer (PCa). Leptin would have a stimulating effect on prostate cancer cells by inducing promotion and progression, whereas adiponectin would have a protective effect. The aim of this study was to determine the relation between body composition, leptin, and adiponectin levels with the prevalence and aggressiveness of PCa in men of Mendoza, Argentina. Seventy volunteers between 50 and 80 years (35 healthy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…In endometrial cancer, a positive association with leptin was found for two studies, though in one this relationship disappeared after adjusting for BMI (76,77). For prostate cancer, leptin does not appear to increase overall risk (78,79, 80) however, it may be linked with more aggressive disease (81). In addition, recent studies suggest that absolute levels of leptin may not be the driving force behind neoplasia, but rather it is the ratio of higher leptin in the presence of low adiponectin that confers risk (82).…”
Section: Adipokinesmentioning
confidence: 99%
“…In endometrial cancer, a positive association with leptin was found for two studies, though in one this relationship disappeared after adjusting for BMI (76,77). For prostate cancer, leptin does not appear to increase overall risk (78,79, 80) however, it may be linked with more aggressive disease (81). In addition, recent studies suggest that absolute levels of leptin may not be the driving force behind neoplasia, but rather it is the ratio of higher leptin in the presence of low adiponectin that confers risk (82).…”
Section: Adipokinesmentioning
confidence: 99%
“…Moreover, the stimulatory effects of leptin on cancer growth may also be due to its angiogenic property [86]. Leptin modulates angiogenesis by increasing the expressions of several angiogenic growth factors such as vascular endothelial growth factor, transforming growth factor β-1 and basic fibroblast growth factor [87]. In Japan, a study indicated that leptin was directly associated with increased colorectal cancer risk independent of body mass index in women [88].…”
Section: Adipocytes In the Cancer Microenvironmentmentioning
confidence: 99%
“…A recent in vitro study suggested an association between obesity‐associated hyperleptinemia and an increased risk for CaP, but further investigations are necessary to clarify whether these data have clinical relevance for use as a prognostic marker for predicting CaP risk (Hoda et al, 2010). It has been observed that body composition and leptin are related to the CaP aggressiveness, but not with its prevalence (López Fontana et al, 2011). A study showed that leptin might not be a surrogate marker of aggressiveness of CaP associated with raised serum leptin, which is independent of obesity and serum prostate‐specific antigen (PSA; López Fontana et al, 2011).…”
Section: Obesity Leptin Level and Prostate Healthmentioning
confidence: 99%
“…It has been observed that body composition and leptin are related to the CaP aggressiveness, but not with its prevalence (López Fontana et al, 2011). A study showed that leptin might not be a surrogate marker of aggressiveness of CaP associated with raised serum leptin, which is independent of obesity and serum prostate‐specific antigen (PSA; López Fontana et al, 2011). It hints at the role of leptin in pathogenesis of this tumor; however, for validation, further studies, including a large patient population, are required.…”
Section: Obesity Leptin Level and Prostate Healthmentioning
confidence: 99%